Tumor Progression and Metastasis 2020
DOI: 10.5772/intechopen.88519
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Photodynamic Therapy Using Ruthenium(II) and Os(II)-Based Complexes as Photosensitizers

Abstract: Photodynamic therapy (PDT) is an approved procedure using a photosensitizer (PS) activated by light to selectively destroy malignant/premalignant cells. Transition metal complexes, such as Ru(II)-and Os(II)-based PSs (Theralase Technologies Inc., Ontario. Canada), are activated in a wide range of wavelengths, are resistant to photobleaching and have a high singlet oxygen quantum yield and ability to produce cytotoxic reactive oxygen species (ROS). Their design allows fine-tuning of the photophysical and photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Therefore, it is important to develop alternative PSs. Among others, the use of transition metal complexes with non-tetrapyrrolic ligands is gaining attention [ 34 , 35 , 36 ]. For example, the Ru(II) polypyridine complex TLD-1433 ( Figure 4 ) entered phase II clinical trials against non-muscle invasive bladder cancer (ClinicalTrials.gov Identifier: NCT03053635) [ 37 , 38 ].…”
Section: Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to develop alternative PSs. Among others, the use of transition metal complexes with non-tetrapyrrolic ligands is gaining attention [ 34 , 35 , 36 ]. For example, the Ru(II) polypyridine complex TLD-1433 ( Figure 4 ) entered phase II clinical trials against non-muscle invasive bladder cancer (ClinicalTrials.gov Identifier: NCT03053635) [ 37 , 38 ].…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Progress has been made over the years on investigating TM-complexes as triplet PSs alternatively to currently accepted PSs, for applications such as PDT [ 34 , 35 , 36 ]. It was shown that the introduction of metal ions into clinically accepted PSs could sometimes overcome the present limitations and drawbacks [ 64 , 65 ].…”
Section: Transition Metal Triplet Photosensitizersmentioning
confidence: 99%
“…Non-specific localization can result in the activation of the phototherapeutic effects off-target, and thus, in PDT applications, damage to the surrounding cells. 37 , 38 The mechanism of cellular uptake of ruthenium complexes can vary depending on complex properties, such as its size, charge, and lipophilicity. 39 Increasing the lipophilicity of a ruthenium complex should increase the uptake via passive diffusion as was demonstrated by Park and co-workers.…”
Section: Introductionmentioning
confidence: 99%